Georg Henisch y la recepción de los 'progymnasmata' en el siglo XVI - Rodríguez Herrera, Gregorio (2017)
In this article, we analyse Georg Henrisch 'progymnasmata' in order to determine his originality within the rhetorical tradition. We will seek to show that this contribution to the tradition of the 'progymnasmata' reflects his pedagogical principles and his academic and religious tolerance.
Keywords: Erasmus, Desiderius, -- 1467-1536; Henisch, Georg, -- 1549-1618; Humanismo; Retórica